Conservation and management practices of traditional crop genetic diversity by the farmers: a case from Kailash Sacred Landscape, Nepal - Aryal, Kamal; Poudel, Sushmita; Chaudary, Ram Prasad; Chettri, Nakul; Ning, Wu; Shaoliang, Yi; Kotru, Rajan (Journal of Agriculture and Environment, 2018)
Crop genetic diversity has been an important source of subsistence livelihoods and nutrition in the remote Himalayan region for local communities. This study documents the crop diversity, their current status and farmer’s knowledge and practices. Study was based on analysis of one local crop diversity fair, 18 key informant surveys, nine focus group discussions and 195 individual household surveys with set questionnaires. The community structure in the study area has female dominance (52%) with average family size of 7.1. The study documents 78 species of various crops which were used as food, vegetables, fruits, medicine, and spices. Highest varietal diversity was recorded in Maize (15), Paddy (12), wheat (11), and beans (10). However, a number of crop varieties are being lost and threatened over the time. Both anthropogenic and natural drivers of changes were reported as the major reason of such loss. Despite loss of crop varieties farmers have been maintaining a wide range of crop and varietal diversity in situ on farm by their own initiatives and experiences. Our study showed that self-saved seed contributed as the major source of planting material through which they are maintaining the crop diversity. However, a detailed study on the seed supply system is needed to support easy access to the farmers. More awareness raising program as well as empowerment of farming communities is essential for the continuation of conservation and management practices.